2007
DOI: 10.1080/10410230701307550
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Women's Preferences for Breast Health Information: Subjective Cultural Influences on Source, Message, and Channel

Abstract: The purpose of this study was to investigate the influence of 3 subjective cultural variables--self-construals (independence and interdependence), ethnic identity (bicultural, assimilation, traditional, and marginal), and cultural health attributions (equity and behavioral-environmental attributions)--on source, message, and channel preferences for receiving breast health information by Hispanic women age 35 or older. Subjective cultural variables collectively accounted for 2% to 28% of the variance in communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Which park the individual visited, his or her race/ethnicity, sex, and native language all significantly predicted external causal attribution (RQ2). While other individual-level variables not explored in this paper (e.g., risk perception) may also help explain variance in causal attribution, the data presented support the idea that attributions may not be universally held, but rather may vary on the basis of cultural background (Menon et al, 1999;Oetzel, DeVargas, Ginossar, & Sanchez, 2007). The differences observed provide some evidence that visitors may arrive with certain predefined assumptions about their role in ensuring their own safety, as well as tendencies toward making causal attributions-beliefs that may render them more or less receptive to park management and communication.…”
Section: Differences Within Groups: Experience and Beyondsupporting
confidence: 60%
“…Which park the individual visited, his or her race/ethnicity, sex, and native language all significantly predicted external causal attribution (RQ2). While other individual-level variables not explored in this paper (e.g., risk perception) may also help explain variance in causal attribution, the data presented support the idea that attributions may not be universally held, but rather may vary on the basis of cultural background (Menon et al, 1999;Oetzel, DeVargas, Ginossar, & Sanchez, 2007). The differences observed provide some evidence that visitors may arrive with certain predefined assumptions about their role in ensuring their own safety, as well as tendencies toward making causal attributions-beliefs that may render them more or less receptive to park management and communication.…”
Section: Differences Within Groups: Experience and Beyondsupporting
confidence: 60%
“…Oetzel et al (81) studied the influence of independence and interdependence, ethnic identity (bicultural, assimilation, traditional, and marginal), and cultural health attributions (equity and behavioral-environmental attributions) on source, message, and channel preferences for receiving breast health information by middleaged or older Latinas. The researchers found that these three subjective cultural factors were significantly related to a variety of audience preferences in terms of source of communication, channels, and fear messages.…”
Section: The Communication-persuasion Modelmentioning
confidence: 99%
“…The new arrivals as well as the first generation Hispanics adapting to the host culture will be more likely to seek out information to assist them in their purchase decisions. For example, studies of Hispanics in the context of health information usage recommend creation of mass media programs including audio-visual and print media as effective tools for persuading the Hispanic audience (Kar et al, 2001;Freimuth and Quinn, 2004;Oetzel et al, 2007). Thus, informative ads may be more useful and hence more liked, but because they are lacking in terms of entertainment appeal, they may be forwarded less by Hispanic consumers.…”
Section: Informative Appealsmentioning
confidence: 99%